1994
DOI: 10.1177/106002809402801011
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin: A New Agent for the Management of Epilepsy

Abstract: Gabapentin appears to be a useful new AED. Further studies evaluating its use as monotherapy, in higher dosages, and in pediatric and elderly patients are required to better delineate its therapeutic role relative to that of other AEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 27 publications
0
25
0
1
Order By: Relevance
“…Although GBP is structurally related to GABA, its antiepileptic activity appears unrelated to any direct effects on the GABA system [51]. GBP is characterized by distinct pharmacokinetic features that provide clinical advantages for its use.…”
Section: Gabapentinmentioning
confidence: 99%
“…Although GBP is structurally related to GABA, its antiepileptic activity appears unrelated to any direct effects on the GABA system [51]. GBP is characterized by distinct pharmacokinetic features that provide clinical advantages for its use.…”
Section: Gabapentinmentioning
confidence: 99%
“…3) was first shown to be an effective anticonvulsant agent in different animal models of epilepsy [154]. In humans, it prevents partial and generalized tonicclonic seizures when prescribed as monotherapy or with other drugs [155][156][157]. In animal models, gabapentin appears to block nociceptive responses, producing analgesic effects, and to possess anxiolytic-like activity [158].…”
Section: Introductionmentioning
confidence: 99%
“…Gabapentin is a novel anticonvulsant which was released for use in epilepsy in 1993 [8,9]. Initial case reports have indicated that gabapentin could be effective in patients with trigeminal neuralgia [10], refractory neuropathic pain [11], postherpetic neuralgia [12] or severe reflex sympathetic dystrophy [13], and that it has a good safety profile.…”
Section: Introductionmentioning
confidence: 99%